Pharmacological inhibition of TRPM4 hyperpolarizes vascular smooth muscle - Gonzales, Albert L. (American Physiological Society, 2010)
The contractile state of vascular smooth muscle cells is regulated by small changes in membrane potential that gate voltage-dependent calcium channels. The melastatin transient receptor potential (TRP) channel TRPM4 is a critical mediator of pressure-induced membrane depolarization and arterial constriction. A recent study shows that the tricyclic compound 9-phenanthrol inhibits TRPM4, but not the related channel TRPM5. The current study investigated the specificity of 9-phenanthrol and the effects of the compound on pressure-induced smooth muscle depolarization and arterial constriction. Patch-clamp electrophysiology revealed that 9-phenanthrol blocks native TRPM4 currents in freshly isolated smooth muscle cells in a concentration-dependent manner (IC(50) = 10.6 μM). 9-Phenanthrol (30 μM) had no effect on maximum evoked currents in human embryonic kidney cells expressing recombinant TRPC3 or TRPC6 channels. Large-conductance Ca(2+)-activated K(+), voltage-dependent K(+), inwardly rectifying K(+), and voltage-dependent Ca(2+) channel activity in native cerebral artery myocytes was not altered by administration of 9-phenanthrol (30 μM). Using intracellular microelectrodes to record smooth muscle membrane potential in isolated cerebral arteries pressurized to 70 mmHg, we found that 9-phenanthrol (30 μM) reversibly hyperpolarized the membrane from ∼−40 mV to ∼−70 mV. In addition, we found that myogenic tone was reversibly abolished when vessels were exposed to 9-phenanthrol. These data demonstrate that 9-phenanthrol is useful for studying the functional significance of TRPM4 in vascular smooth muscle cells and that TRPM4 is an important regulator of smooth muscle cell membrane depolarization and arterial constriction in response to intraluminal pressure.